Epigenetic alterations—The silent indicator for early aging and age‐associated health‐risks. Issue 4 (20th December 2022) - Dhar, Poulami; Moodithaya, Shailaja S.; Patil, Prakash
Abstract: Aging is the process of gradual physiological deterioration till death and this process perpetually reduce the functionality of an individual. To address the rationale and provide geriatric care, the constant target of geroscience is to identify reliable biomarkers for aging. Over the past decades, diversified advancements in epigenetic studies crescively support the fact that the accumulation of epigenetic changes accompanies the process of aging. A growing number of studies have suggested that alterations occur through three fundamental mechanisms like methylation of DNA, histone protein modification, and production of non‐coding microRNAs. Each of these changes occurs silently and provokes alterations in the circumstantial expression of genetic material without altering the underlying gene sequences. The changes in gene expression due to epigenetic alterations are suggested to be the cause of early aging and the onset of age‐related health risks. This review would attempt to give an integrated overview of epigenetic changes related to aging and age‐associated health risks. This review also discussed epigenomes influencing early aging and factors modulating it. Since epigenetic changes are reversible, early identification of epigenetic markers can be a hope for future geriatric medicine. Finally, this review emphasizes the identification of blood‐based epigenetic biomarkers in order to enlighten the future scope for therapeutic intervention to slow down the aging process. Abstract : An epigenetic alteration like DNA methylation, Histone modification, or miRNA production can potentially influence an individual's genetic expression without changing their sequence. The change in epigenome‐induced genetic alteration can cause early aging and age‐related health risk. This is an informative mini‐review to summarize the fact behind epigenetics and aging.